Model-Based Reasoning in the Deductive Laboratory Work with Arduino and Sensor Module - Soka Hadiati; Dwi Fajar Saputri; Wahyudi Wahyudi; Adi Pramuda (Universitas Lambung Mangkurat, 2021)
Laboratory work that has been applied so far is more dominant in deductive laboratory work, but this type of laboratory work is not optimal in stimulating students' reasoning ability. Up to now, model-based reasoning studies on laboratory work have been substantial (especially in measurement and troubleshooting activities) and have not seen overall laboratory activity, including the use of alternative instrumentation such as Arduino and its sensor module. Designing the best laboratory work requires the role of model-based reasoning studies using Arduino devices. A mixed-method research design was used in this study with a theoretical study to obtain a predictive pattern for deductive laboratory work model which was matched with the observations of 50 undergraduate physics education students in laboratory work. Revision activities were shown by students in laboratory work depending on the capabilities of reasoning. The results of this study indicate that revision activities in deductive laboratory work using Arduino can stimulate students' reasoning. Arduino can lead students to explore their thinking and reasoning to solve problems in laboratory work.